2020
DOI: 10.4103/iju.iju_344_19
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of standard 12-core transrectal ultrasound-guided prostate biopsy in biopsy naive Indian men -single center experience

Abstract: Introduction: Prostate cancer is now the second-most common cancer in many parts of India. Despite being the second-largest population in the world, data regarding outcomes of biopsy in Indian men are limited. We report the correlation of biopsy finding with prostate-specific antigen (PSA) level in Indian men undergoing biopsy for either elevated PSA and/or abnormal digital rectal examination (DRE) findings. Materials and Methods: We retrospectively analyzed data of 853… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…Comparison of previous studies are shown in table S2 which had a PCa rate of 8.7-44.8% [5,[7][8][9][10]. In a previous study from Sri Lanka, the prevalence of PCa in 749 symptomatic males subjected to TRUSPB was 35.2%, which was lower than the current study [5].…”
Section: Discussionmentioning
confidence: 47%
“…Comparison of previous studies are shown in table S2 which had a PCa rate of 8.7-44.8% [5,[7][8][9][10]. In a previous study from Sri Lanka, the prevalence of PCa in 749 symptomatic males subjected to TRUSPB was 35.2%, which was lower than the current study [5].…”
Section: Discussionmentioning
confidence: 47%
“…Vascular complications, such as intraoperative injury to blood vessels, which results in massive bleeding, are commonly reported complications of radical cystectomy, which is a catastrophic event and may potentially have an unfavorable effect on surgical mortality rates (4,5). Iliac artery pseudoaneurysm and arterioureteral fistula are rare complications following radical cystectomy (6,7). The present study described another rare case of delayed right external iliac artery disruption that occurred one month after laparoscopic radical cystectomy, without any obvious evidence of iliac artery pseudoaneurysm or arterioureteral fistula.…”
Section: Introductionmentioning
confidence: 99%